Estudo das propriedades estruturais e dielétricas da matriz cerâmica BiVO4 e os efeitos da adição de Tio2 e CaTiO3 para aplicações em engenharia de micro-ondas - Oliveira, Ronaldo Glauber Maia de (2019)
In this study the structural and dielectric properties of the ceramic matrix monoclinic phase BiVO4 (BVO) were investigated with mass addition of titanium oxide (TiO2) in the proportions of 8, 16, 24, 28 and 32wt.%, and calcium titanate (CaTiO3) of 15, 30, 45, 55 and 60wt.%. The solid-state reaction method was used for the production of powders BVO. After calcination at 500ºC, X-ray diffraction analysis was performed to characterize the structure and composition of the samples, proven through refinement Rieteveld. The samples were pressed in the form of cylinders at 800ºC. The study of the morphology was performed through Scanning Electron Microscopy (MEV) and the samples were compared using the density measurements obtained through the pycnometry. The dielectric characterization was performed in the radiofrequency regions (RF) and microwave (MW). A study of properties with temperature variation was made through possible application in RF and MW. The main objective was to obtain ceramic dielectric components with high dielectric constant, low dielectric losses, thermal stability, good bandwidth, gain and efficiency. At ambient temperature at 1Hz in RF, a giant dielectric constant value was identified (ε’ = 2,6x104 ), higher than the values found in the literature, of the order of 102 at a frequency of 10 Hz, and tangent of dielectric losses (tg ) of the order of 10-1 . From the analysis of the behavior in MW, obtained using the Hakki-Coleman, it was possible to verify a dielectric constant of 67 in the pure sample and 15,75 in the addition of 32% of CaTiO3 (CTO) tangent of dielectric losses in the order of 10-3 . The measurement of the temperature coefficient of the resonant frequency (f) showed the possibility of achieving thermal stability (f = 0). There was obtained f = - 244,02 ppm/°C to BVO and -69 ppm/°C and -2,75 ppm/°C for the addition of 22,8% of TiO2 and 16% of CTO, respectively. From 16% of CTO, the values of f oscillate between -79.06 and -43.99 ppm/°C, while the addition of TiO2 kept growing. Numerical simulations were performed showing reasonable agreement with the experimental data. Ceramics are useful for application in antenna devices, in satellite communications systems, radar, radio reception.